2014
DOI: 10.1007/s00540-014-1818-6
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin system as a target in sepsis?

Abstract: The nociceptin system comprises the nociceptin receptor (NOP) and the ligand which binds to the receptor (N/OFQ). The archetypal role of the system is in pain processing but it is also expressed on immune cells. Activation of the NOP receptor is known to modulate inflammatory responses such as mast cell degranulation, neutrophil rolling, vasodilation, increased vascular permeability, regulation of adhesion molecules and recruitment of leucocytes. As there is a loss of regulation of inflammatory responses durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…However, early recognition is not always easy as typical signs and symptoms are not always obvious in all critically ill patients. There has been a concerted effort from both clinical and basic researchers to address this issue of recognition with several studies attempting to establish early diagnostic criteria [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early recognition is not always easy as typical signs and symptoms are not always obvious in all critically ill patients. There has been a concerted effort from both clinical and basic researchers to address this issue of recognition with several studies attempting to establish early diagnostic criteria [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggest that neuronal bioactive substances such as nociceptin [4] and endocanabinoid [6] may contribute to the pathophysiology of sepsis. Several reports [7][8][9] suggest that orexin (OX) may also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Our results uncovered a novel anti-nociceptive phenotype in septic mice. Altered pain perception has previously been reported in sepsis patients (Thomas, Stover, Lambert, & Thompson, 2014), and increased sensitivity to deep pain but not cutaneous pain has been reported in studies of human experimental endotoxemia (Karshikoff et al, 2015).…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies have reported that the nociceptin/orphanin FQ peptide (NOP) opioid receptor and its endogenous agonist, Noc, are involved in sepsis and the observed inflammatory responses [ 16 , 17 ]. Thus, we next examined the Noc concentration-response relationships for both groups of CSMG neurons.…”
Section: Resultsmentioning
confidence: 99%